2022
DOI: 10.21037/atm-21-4779
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid B alleviates neurological injury by upregulating stanniocalcin 1 expression

Abstract: Background Salvianolic acid B (Sal B) is a representative component of phenolic acids derived from the dried root and rhizome of Salvia miltiorrhiza Bge. (Labiatae), which promotes angiogenesis in myocardial infarction and diabetic cardiomyopathy. However, whether Sal B has a neuroprotective function in ischemic stroke by promoting angiogenesis is still unclear. Methods In the present study, ischemic stroke models were induced in rats by middl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…26 Increasing the expression of STC1 can promote angiogenesis and reduce neuronal apoptosis. 27 However, the impact of STC1 on the blood−brain barrier remains unclear. 28,29 A prospective cohort study found that the serum concentrations of STC1 were increased in intracerebral hemorrhage patients and independently predicted a poor prognosis.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Increasing the expression of STC1 can promote angiogenesis and reduce neuronal apoptosis. 27 However, the impact of STC1 on the blood−brain barrier remains unclear. 28,29 A prospective cohort study found that the serum concentrations of STC1 were increased in intracerebral hemorrhage patients and independently predicted a poor prognosis.…”
Section: ■ Discussionmentioning
confidence: 99%
“…There is a lack of clinical research on the association of STC1 with IS, but preclinical studies suggest that it is involved in neuroprotection after ischemia, thereby participating in functional recovery after IS . Increasing the expression of STC1 can promote angiogenesis and reduce neuronal apoptosis . However, the impact of STC1 on the blood–brain barrier remains unclear. , A prospective cohort study found that the serum concentrations of STC1 were increased in intracerebral hemorrhage patients and independently predicted a poor prognosis .…”
Section: Discussionmentioning
confidence: 99%
“…The above results suggest that there is a close relationship between neurons and ECs in the process of angiogenesis, and angiogenesis often promotes the recovery of neurological function after cerebral ischemia. Moreover, studies report that postischemic angiogenesis follows a temporal course (Bi et al., 2022; Zhang et al., 2009). ECs begin mitosis as early as 1 day after mouse cerebral reperfusion after 30 min of MCAO, and the number of vessels begins to significantly increase on the 3 days before peaking at 7 days after stroke (Yang et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In an experiment on middle cerebral artery occlusion-induced ischemic stroke rats, salvianolic acid B attenuated ischemic brain injury and neurological injury by increasing stanniocalcin 1 (STC1), thus inducing Akt/mTOR phosphorylation and the upregulation of VEGF and VEGF receptor 2 (VEGFR2), which promoted angiogenesis and protected against neuronal apoptosis [ 56 ]. In addition, salvianolic acid B can enhance the autophagic activity of astrocytes by activating the adenosine 5′-monophosphate-activated protein kinase (AMPK)/mTOR/Unc-51-like kinase 1 (ULK1) signaling pathway and promoting the autophagic degradation of pS757-ULK1, thus playing a neuroprotective role in cerebral ischemic injury.…”
Section: Pharmacological Effectsmentioning
confidence: 99%